Analisis Eksperimental Kekuatan Sambungan Konvensional dan Futuristik dalam Konstruksi Furnitur: Experimental Analysis of Conventional and Futuristic Joint Strength in Furniture Construction - Soleh Muhamad; Bahtiar Rahmat; Agung Ari Purwanto; Wahyu Widiyanto; Arip Wijayanto; Desy Mulyosari; Nurmadina Nurmadina (JURNAL HUTAN TROPIKA, 2026)
This study aims to evaluate the strength of conventional and innovative joints in MDF furniture construction through compression testing. The four types of corner joints tested include Lamello biscuit joints, Minifix joints, wood dowel joints, and JCBC insert nut joints. Each joint type was tested under two loading conditions using the diagonal compression method. Test results indicate that the futuristic JCBC insert nut joint and the conventional wood filler joint exhibited the highest compressive strength, while the futuristic Minifix joint and the conventional Lamello biscuit joint demonstrated the lowest compressive strength performance under both the A-shaped and L-shaped test configurations. Statistical analysis of the density and moisture content of the MDF revealed no significant differences among all specimens; thus, the differences in compressive strength were primarily influenced by the type of joint. These findings provide practical recommendations for the furniture industry in selecting the optimal joint based on efficiency and structural strength, with wood fillers (conventional joints) used for knock-up furniture and JCBC insert nuts (futuristic joints) used for knock-down furniture as the best alternatives for furniture construction joints.